Neurological manifestations in dogs naturally infected by Leishmania infantum: descriptions of 10 cases and a review of the literature. (March 2017) - Giannuzzi, A. P.; Ricciardi, M.; De Simone, A.; Gernone, F.
Abstract : In order to evaluate possible nervous system involvement in canine leishmaniasis, retrospective evaluation of all medical records of leishmaniotic dogs exhibiting neurological signs referred to our hospital over a 5‐year period was performed. The records of 10 dogs were reviewed. Depending on the neuroanatomical localisation, the dogs underwent advanced diagnostic imaging, cerebrospinal fluid analysis, electrodiagnostic testing and histopathologic evaluations. The final neurological diagnosis was: meningoencephalitis (n=2), brain haemorrhagic stroke (n=1), haemorrhagic choroiditis (n=1), meningomyelitis (n=2), ischaemic myelopathy (n=1), polymyositis (n=2) and peripheral neuropathy (n=1). This study confirms that both central and peripheral nervous systems can be affected by leishmaniasis and provides an overview on the possible etiopathogenetic mechanisms. In addition, clinical and diagnostic findings, therapy and follow‐up of affected dogs are described.